ESTABLISHMENT THE FACTORS INFLUENCING THE PROCESS OF WASHING MILK - Палій, А. П. (Scientific Progress & Innovations, 2015)
High-quality washing milking equipment along with the use of highly efficient technologies and equipment is a critical factor in obtaining of high quality milk. It has been established that there are three basic methods of forming plugs in a milk cleaning solution, formation mechanisms which depend on the design of the washing machine and the program for the implementation of selected processing operation. The results are a prerequisite of improving the system of control the parameters of milking cattle and washing milking equipment.